AN EDUCATIONAL STUDY ON FINANCIAL SYNERGY WITH SPECIAL REFERENCE TO EMAMI AND KESH KING COMPANIES COMBINATION - Sub Lt. Devika A; Vani S D, Kavitha; Latha R; Ramesha V (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The business concerns have the best practices. One of the best practices is acquisition of best small company by the big companies. This provides benefit to both the selling company as well buying companies. One the popular company doing such acquisitions is Emami. It is expanding its product portfolio through major acquisitions. Its major acquisitions includes Himami acquisition in 1978, Zandu acquisition in 2008, Kesh King acquisition 2015, Crème 21 acquisition in 2018. Kesh King was set up by Mr. Sanjeev Juneja with just Rs. 2,000 in 2001 year. He got motivation from his father’s ayurvedic clinic and experimented a herbal mix and started Kesh King, He went to door to door and many retail outlets to sell his product Kesh King, one of ayurvedic oil for hair fall problem. But he was rejected several times. But, did not gave up his attempt, he got success and popularize his brand. His product has become very popular Indian FMCG sector covering 35% market share. In 2015, Emami kept an eye and acquired the entire prodct portfolio and entire buyout takes place for Rs. 1,651 crores. This benefited both companies. The data has been collected from secondary sources like daily newspapers, journals and magazines and internet sources. The paper concludes that synergitic benefits must be enjoyed with positive combinations.